Effect of heat treatment on thermodynamics parameters, crystal and microstructure of (Cu-Al-Ni-Hf) shape memory alloy - Qader, Ibrahim Nazem; Kok, Mediha; Dagdelen, Fethi (Elsevier Science Bv, 2019)
A quaternary Cu80Al13Ni3Hf4 (wt%) shape memory alloy has been produced from high pure metallic powder through arc-melting method. Then homogenization been performed at 1173 K for 24 h and followed by a rapid cooling to salt-iced water. As a technique, one hour heat treatment at 773 K, 873 K, 973 K, 1073 K, and 1173 K, has been done to investigate some physical and structural properties. Some relevant measurements by using DSC, XRD, EDX-SEM, and Vickers hardness devices has been accomplished. While both DSC and XRD results showed that in room temperature all specimens were in austenite phase, but increasing the temperature of heat treatment make changes in the amount of precipitations presented in SEM micro-images, and hence led to a decrease in microhardness values. The sample with 1173 K heat treatment was the more stable phase compared to the other specimens, because a minimum values was obtained in calculation of Gibbs free energy and entropy.
Keywords: Hafnium; Copper based shape memory alloy; Heat treatment; Martensitic phase transformation; Low temperature shape memory alloy; DSC